2012
DOI: 10.2136/vzj2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

Microtopography as a Driving Mechanism for Ecohydrological Processes in Shallow Groundwater Systems

Abstract: Microtopography can have a large eff ect on fl ow processes at the soil surface and the composi on of soil water. Microtopography is o en represented by a roughness parameter in hydrological models. In areas without a strong topographical gradient, microtopography may be underes mated when accumulated in a single parameter, especially in shallow groundwater systems. This study reviews the intricate rela onships between microtopography, surface runoff , and ecohydrology in systems featuring shallow water tables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 92 publications
1
38
0
1
Order By: Relevance
“…Recent studies have shown that greenhouse gas fluxes, in particular of methane, strongly depend on the micro-topographic features of such environments (Gong et al, 2013;Couwenberg and Fritz, 2012), and that local hydrology is regulated by micro-relief (Shi et al, 2015;Gong et al, 2012;Bohn et al, 2013;Van der Ploeg et al, 2012). In particular, a typical feature of methaneemitting landscapes is the nonlinear relationship between fluxes and emitting surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that greenhouse gas fluxes, in particular of methane, strongly depend on the micro-topographic features of such environments (Gong et al, 2013;Couwenberg and Fritz, 2012), and that local hydrology is regulated by micro-relief (Shi et al, 2015;Gong et al, 2012;Bohn et al, 2013;Van der Ploeg et al, 2012). In particular, a typical feature of methaneemitting landscapes is the nonlinear relationship between fluxes and emitting surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic boundary of water table induces changes between aerobic and anaerobic status and also influences R s through soil water content (SWC) or substrate availability to biological processes [Wheeler, 1999]. Microtopography, interacting with hydrologic regime, is associated with plant distributions and soil chemical and physical properties [Ehrenfeld, 1995;Frei et al, 2012;Jones et al, 1996;Van der Ploeg et al, 2012;Waddington and Roulet, 1996]. However, only a few studies included the microtopography factor into the design of field experiments, which could significantly affect the estimate of R s at the ecosystem scale and the role of wetlands in the global carbon cycle [Alm et al, 1997[Alm et al, , 1999Jauhiainen et al, 2005;Luken and Billings, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…The role of soil surface on water flow was addressed in the paper of Van der Ploeg et al (2012). For a wetland ecosystem they showed that microtopographic variations create complex patterns of water ponding and redistribution, affecting water flow and solute transport, and creating niches for different plant species.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…While in the vertical direction the extent of the vadose zone is limited by the presence of a usually water‐saturated aquifer, length scales in lateral direction are much larger (Harter and Hopmans, 2004), with heterogeneities defined by soil association, vegetation types, and topography at regional or catchment scale (Wagenet, 1998; Western et al, 2001; Vogel and Roth, 2003). In this special section we limit the upper range of scales by the “radius of influence” of a heterogeneity in soil texture or surface topography on lateral water flow that is within the range of a few meters (Lehmann and Or, 2009; van der Ploeg et al, 2012). Because an accurate description of the water distribution in the vadose zone can only be achieved by a more complete understanding of dynamics at the pore scale, the smallest scale addressed in this special section is the pore scale.…”
mentioning
confidence: 99%